2008
DOI: 10.1364/oe.16.003191
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency NbN nanowire superconducting single photon detectors fabricated on MgO substrates from a low temperature process

Abstract: . (2008). High efficiency NbN nanowire superconducting single photon detectors fabricated on MgO substrates from a low temperature process. Optics Express, 16(5), 3191-3196. DOI: 10.1364/OE.16.003191 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 15 publications
4
54
0
Order By: Relevance
“…We previously developed a low-temperature deposition process ͑T S = 400°C, quenched growth͒ on MgO, which yielded high quality NbN thin films. 8 However, films deposited on GaAs at T S = 400°C did not reach the same quality as the films on MgO. 11 We found that the reason of this degradation was that, at 400°C, As oxide ͑AsO and As 2 O 3 ͒ evaporated from the GaAs substrate during the baking ͑6-8 h͒ and the deposition procedure ͑30 min͒, which resulted in poor morphology of the substrate surface and thus of deposited films.…”
Section: Nanowire Superconducting Single-photon Detectors On Gaas Formentioning
confidence: 96%
See 2 more Smart Citations
“…We previously developed a low-temperature deposition process ͑T S = 400°C, quenched growth͒ on MgO, which yielded high quality NbN thin films. 8 However, films deposited on GaAs at T S = 400°C did not reach the same quality as the films on MgO. 11 We found that the reason of this degradation was that, at 400°C, As oxide ͑AsO and As 2 O 3 ͒ evaporated from the GaAs substrate during the baking ͑6-8 h͒ and the deposition procedure ͑30 min͒, which resulted in poor morphology of the substrate surface and thus of deposited films.…”
Section: Nanowire Superconducting Single-photon Detectors On Gaas Formentioning
confidence: 96%
“…Superconducting singlephoton detectors ͑SSPDs͒, 5 based on the photon-induced creation of resistive regions ͑hot spots͒ in nanowires biased close to their critical current, have shown detection efficiencies of up to 30% at = 1.3 m, dark counts in the range of few hertz 5 and are extremely fast ͑with count rates approaching the gigahertz range͒. 6,7 SSPDs have so far been fabricated only on sapphire, 5 MgO, 8 and Si 9 substrates, which are not suitable for the integration with single photon sources. The fabrication of SSPDs on GaAs would enable integration with all the circuitry required for photonic quantum information processing, since GaAs readily lends itself to the largescale production of single-photon sources, 10 waveguides, interferometers, and phase modulators.…”
Section: Nanowire Superconducting Single-photon Detectors On Gaas Formentioning
confidence: 99%
See 1 more Smart Citation
“…SSPDs are typically made by patterning a meander-type nanostructure in an ultrathin (≈ 5 nm) film deposited on a sapphire [1], MgO [7], or, recently, 3C-SiC/Si [8] single-crystal substrates. Single-crystal quality NbN films are deposited by either DC or RF reactive magnetron sputtering on substrates maintained at the 700-850…”
Section: Introductionmentioning
confidence: 99%
“…To directly observe such relaxation bottleneck effects, superconducting single photon detectors (SSPDs) are suitable due to their near unity quantum efficiency and picosecond timing resolution 10,11 . Building up on recent progress in this field 12-14 , we developed highly efficient 15,16 NbNSSPDs on GaAs 17 and demonstrated the monolithic integration of InGaAs QDs as single photon emitters together with waveguides and detectors on a single chip 18 . In this letter, we compare photoluminescence (PL) dynamics recorded from a single dot with confocal off-chip detectors with on-chip PL using integrated SSPDs that provide temporal resolution better than 70 ps.…”
mentioning
confidence: 99%